Increasing the Economic Value of Bamboo Shoots through Candied Products as a Typical Product of Masaran Village - Setiawan, Angga; Fudin, Muhammad Soleh; Putra, Reda Firnanda; Rizhin, Alpha; Oktavia, Fadila Fitri (CV Media Inti Teknologi, 2025)
This community service program aimed to increase the economic value of bamboo shoots (rebung) by training the community of Masaran Village to produce candied bamboo shoots as a distinctive local product. The activity focused on empowering housewives with unused time to become productive contributors to their household economy. The methods involved five main stages: planning, preparation, implementation, evaluation, and reporting. The implementation phase included theoretical and practical training on the selection of raw materials, processing techniques, packaging, and marketing strategies. Through interactive discussions and demonstrations, participants were equipped to transform bamboo shoots-previously sold cheaply or underutilized-into high-value products. The results showed that the participants gained new skills in food processing and entrepreneurship. Several participants expressed interest in continuing production and expanding sales through local stores and digital platforms. The initiative successfully led to the creation of a small-scale industry of candied bamboo shoots in the village. It also increased community awareness of local resource potential and strengthened women's roles in household economic development. In conclusion, the program enhanced economic resilience through local food innovation and is expected to contribute to long-term sustainable development in Masaran Village.